2012
DOI: 10.1111/j.1365-2966.2012.20301.x
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy triplets in Sloan Digital Sky Survey Data Release 7 - I. Catalogue

Abstract: We present a new catalogue of galaxy triplets derived from the Sloan Digital Sky Survey (SDSS) Data Release 7. The identification of systems was performed considering galaxies brighter than Mr=−20.5 and imposing constraints over the projected distances, radial velocity differences of neighbouring galaxies and isolation. To improve the identification of triplets, we employed a data pixelization scheme, which allows us to handle large amounts of data as in the SDSS photometric survey. Using spectroscopic and pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…O'Mill et al (2012) constructed a catalogue of triplets with their primary galaxies (M r < −20.5) selected from a volume-limited sample in the Sloan Digital Sky Survey Data Release 7 (SDSS-DR7) Abazajian et al (2009) (hereafter O-sample). This catalogue comprises 1092 triplets with redshift range 0.01 ≤ z ≤ 0.14.…”
Section: Introductionmentioning
confidence: 99%
“…O'Mill et al (2012) constructed a catalogue of triplets with their primary galaxies (M r < −20.5) selected from a volume-limited sample in the Sloan Digital Sky Survey Data Release 7 (SDSS-DR7) Abazajian et al (2009) (hereafter O-sample). This catalogue comprises 1092 triplets with redshift range 0.01 ≤ z ≤ 0.14.…”
Section: Introductionmentioning
confidence: 99%
“…In O'Mill et al (2012) (hereafter paper I) we present a method to identify triplets of galaxies in the Seventh Data Release of the Sloan Digital Sky Survey. In Duplancic et al (2013) (hereafter paper II) we analyse the properties of galaxies in a sample of isolated triplets of bright galaxies and found that these systems could be considered as an analogous of compact groups with a lower number of members.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we have used the algorithm described in O'Mill et al (2012) to identify isolated galaxy triplets in a volumelimited sample (Mr < −20.5 + 5 log h70) from the Sloan Digital Sky Survey Data Release 10. An initial sample of 97 galaxy systems between 0.04 z 0.1 is compiled.…”
Section: Discussionmentioning
confidence: 99%
“…We have obtained a sample of galaxy triplet candidates in the volume-limited sample described in the previous section with the algorithm developed by O'Mill et al (2012).…”
Section: Triplet Identificationmentioning
confidence: 99%
See 1 more Smart Citation